Implementation of the GASING Method in Teaching Parabolic Motion: A Comparative Analysis of Learning Outcomes in Biology Education - Muhammad Taufik; Syahrial A (Universitas Hamzanwadi, 2024)
Teaching of physics concepts to non-physics majors presents significant challenges, particularly when it comes to helping students connect abstract physical principles with their primary field of study. This study investigates the effectiveness of the GASING (Graduated Assistance in Student-led Inquiry and Narrative learning through Guided experimentation) method in teaching parabolic motion to first-semester Biology Education students FKIP Universitas Mataram. Using a quasi-experimental design with two parallel classes (n = 54), we assessed the method’s effectiveness through pre- and post-tests, mini-projects, laboratory observations, and detailed student feedback questionnaires. Results demonstrated significant improvements in conceptual understanding, with mean scores increasing from 4.15 to 7.63 (Class D) and 7.56 (Class E), yielding a substantial effect size (Cohen’s d = 3.26). Both classes showed comparable performance in mini-projects (mean scores: 16.0/20 and 16.3/20). Student feedback across multiple engagement, clarity, and effectiveness measures consistently scored above 4.0/5. Statistical analysis revealed a significant correlation between student engagement and learning outcomes (r = 0.78, p < 0.001). These findings suggest that the GASING method effectively bridges the gap between physics concepts and biological applications while maintaining high student engagement and comprehension